Sulfonamido-derivatives of unsubstituted carbazoles as BACE1 inhibitors. Issue 21 (1st November 2017) - Bertini, Simone; Ghilardi, Elisa; Asso, Valentina; Minutolo, Filippo; Rapposelli, Simona; Digiacomo, Maria; Saccomanni, Giuseppe; Salmaso, Veronica; Sturlese, Mattia; Moro, Stefano; Macchia, Marco; Manera, Clementina
Graphical abstract: Abstract: A novel series of variously substituted N -[3-(9 H -carbazol-9-yl)-2-hydroxypropyl]-arylsulfonamides has been synthesized and assayed for β-Secretase (BACE1) inhibitory activity. BACE1 is a widely recognized drug target for the prevention and treatment of Alzheimer's Disease (AD). The introduction of benzyl substituents on the nitrogen atom of the arylsulfonamide moiety has so far led to the best results, with three derivatives showing IC50 values ranging from 1.6 to 1.9 μM. Therefore, a significant improvement over the previously reported series of N -carboxamides (displaying IC50 's ≥ 2.5 μM) has been achieved, thus suggesting an active role of the sulfonamido-portion in the inhibition process. Preliminary molecular modeling studies have been carried out to rationalize the observed structure-activity relationships.